Isolation, characterization, and herbicidal potential of soil actinobacteria - Gajic Umiljendic, Jelena; Sarić-Krsmanović, Marija; Vasić, Miloš; Šantrić, Ljiljana (Acta herbologica, 2026)
In laboratory conditions, the effect of 22 actinobacteria isolates from arable soil on seed germination and the growth of maize, Setaria glauca, and Sorghum halepense was examined. Suspensions of eight isolates showed varying levels of inhibitory effects on seed germination and seedling growth. Based on the screening results, five actinobacterial isolates exhibited strong inhibition of one or both weed species, with minimal negative impact on maize. The SI I isolate was identified as the best candidate for further testing because the inhibition for maize was less than 18%, while it exceeded 81% for the weeds.